A Study of dispersions for a paraffin-water-surfactant system - Bernal Samaniego, Cesar Augusto (2018)
The propose to study paraffin-water-surfactant was to obtain emulsions that can selfdisperse in water, and which can be made through a low-energy mixing procedure. A first emulsion formulation was carried out with different Tween and Span surfactants, as well as a mixture for obtaining the W/O emulsions (water in oil). Subsequently, a second emulsion formulation was fulfilled, but this time changing the Hydrophilic-Lipophilic Balance (HLB) and/or moderately changing the surfactant or water percentage. Afterwards, the drop size and the stability were studied, and it revealed that more stable emulsions are obtained in thesystems aforementioned using larger amounts of surfactants and a HLB 8.